Penerapan Metode Pembelajaran Bersama Siswa Sekolah Dasar pada Masa Pandemi Covid-19 di Lingkungan Perumahan Nindya Indah, Desa Tonja - I Wayan - Juniartha; Putu Armitha Widiyanthi; Nengah Landra; I Putu Andri Permana (Universitas Negeri Padang, 2022)
This studi aims to know the signifincasies of grup learning method implemented to elementary students in Nindya Indah residence toward their understanding of school learning material during the Covid-19 pandemic situation. The method used in this study is observation method in comprehending the situation of learning process faced by elementary students in Nindya Indah Residence during Covid-19 pandemic. Furthermore, the interview method is implemented in discovering the issues faced by the parents asisting their children to understand the school subject material. And finally, the descriptive qualitative method is conducted to explain the method used in the group learning of elementary students in Nindya Indah Residence. The result showed that there is a significant progress in term of focus and creativity during the implementation of grup learning method.